1999
DOI: 10.1139/f99-064
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk breaks size-dependent dominance in juvenile coho salmon (Oncorhynchus kisutch) and provides growth opportunities for risk-prone individuals

Abstract: Groups of coho salmon (Oncorhynchus kisutch) fry in stream tanks formed size-determined dominance hierarchies, which were upheld through aggressive interactions and led to smaller fish occupying inferior feeding positions. Under simulated predation risk, the frequency of agonistic interactions was reduced, but more intensive aggressive behaviours were performed. This allowed small fish to gain access to better feeding positions. The effect of the predation threat on coho behaviour seemed to extend across a rif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…[28]). The T MT strain containing the OnMTGH1 construct has been used for all simulated stream studies examining ecological effects of GH transgenic coho salmon (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[28]). The T MT strain containing the OnMTGH1 construct has been used for all simulated stream studies examining ecological effects of GH transgenic coho salmon (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Stream tanks generally omit predators. Reinhardt (1999) found that the intensity of agonistic encounters occurring among coho salmon, were affected by predation risk. An increase in simulated predation risk, using an electrified model of a kingfisher, reduced agonistic encounters and allowed smaller fish better access to feeding positions.…”
Section: Increased Social and Environmental Complexitymentioning
confidence: 99%
“…Therefore, the absence of predators may exaggerate physiological variation associated with dominance. Pronounced positive correlations between dominance and growth and dominance and length disappeared when predators were added (Reinhardt, 1999). Structural complexity may influence social interactions.…”
Section: Increased Social and Environmental Complexitymentioning
confidence: 99%
“…It is possible that growth requirements of age I+ coho and steelhead differ, and that age I+ coho accept a slower growth rate in exchange for less predation risk because they will smolt early the following summer. This has been suggested for coho (Reinhardt 1999) and clearly demonstrated for Atlantic salmon (Thorpe et al 1992;Metcalfe 1998;Juanes et al 2000). If this is the case it would be an example of selective segregation based on long-term survival, rather than on short-term energetic, considerations.…”
Section: Discussionmentioning
confidence: 77%